THE URGENCY OF MERGING SPECIAL CRIMES IN REFORMING THE CRIMINAL CODE - Kadir, Abdul; Suparji Achmad (ZILLZELL MEDIA PRIMA, 2023)
The new Criminal Code (KUHP) has been ratified by the government as Law Number 1 of 2023. The formulation of the problem that will be raised in this research is the urgency and legal consequences of combining specific criminal acts in the renewal of the criminal code. and What are the specific types of criminal acts in Law Number 1 of 2023 concerning the Criminal Code. This research uses a normative type of research, using secondary data, namely data obtained directly through library materials. The results of the research concluded that combining general and special criminal law into the new Criminal Code appears to be due to considerations of making the Criminal Code more comprehensive, the urgency of implementing special criminal law will be able to better accommodate the interests of all levels of Indonesian society. There are five types of special crimes in the new Criminal Code, such as serious crimes against human rights, terrorism crimes, corruption crimes, money laundering crimes and narcotics crimes.